Adsorption of Au(III) ions from aqueous solutions by thiol-ene photoclick hydrogels and its application to electronic waste and geothermal water - KÖK YETİMOĞLU, ECE; KAHRAMAN, MEMET VEZİR (ELSEVIER SCIENCE BV, 2014)
This work describes the preparation and characterization of a new thiol-ene hydrogel by photoinitiated polymerization of pentaerythritoltetrakis(3-mercaptopropionate) (Penta3MP4), acrylic acid (AAc) and poly(ethylene glycol) dimethacrylate (PEGDA) as monomers and photo initiator(2,2-dimethoxy-2-phenylacetophenon) for its use as adsorbent. The thiol-ene hydrogel was characterized by using Attenuated Total Reflectance-Fourier Transform Infrared Spectroscopy (ATR-FTIR), Real-Time Fourier Transform Infrared Spectroscopy (RT-FTIR), Scanning Electron Microscopy (SEM), Thermal Gravimetric Analyze (TGA) techniques; the swelling behavior and gelation ratio of hydrogel were also investigated. The adsorption capability of the hydrogel against Au(III) ions was investigated. The effects of pH, agitation time, initial metal ion concentration and different metal ions on adsorption capacity were examined. Equilibrium studies have been carried out to determine the capacity of the hydrogel for adsorption of Au(III) ions, Langmuir and Freundlich adsorption models were applied to describe the experimental isotherms and isotherms constants. Equilibrium data were found to fit very well with Langmuir model. The reusability of the hydrogel was also investigated and the preconcentration factor of the hydrogel was determined. The proposed method was applied to Dikili Geothermal Water and computer circuit board scrap. The analytical performance of the method was also determined. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Au(III) ion; Adsorption; Thiol-ene; Recovery; Computer circuit board scrap; METAL-IONS; SOLVENT-EXTRACTION; GOLD(III); RECOVERY; GOLD; SEPARATION; CHITOSAN; PRECONCENTRATION; RESINS; PALLADIUM(II)